Cost efficiency analysis in the Chinese commercial banking sector - Wang, Yiqiao (2019)
By employing a one-stage SFA estimation model, this paper examines the cost efficiency of 112 Chinese commercial banks between 2013 and 2018 and explores the effects of different variables on cost efficiency. Overall, the average cost efficiency of the Chinese commercial banking sector is 84.15%, and there is an overall diminishing trend of cost efficiency over the sample period. Positive and significant correlations between bank size, GDP growth rate, bank profitability, equity ratio and cost efficiency are found. The results also suggest that foreign banks are more cost efficient than domestic banks, and higher cost efficiency levels are associated with unlisted banks. Technical change and economies of scale are further analysed. Between 2013 and 2018, the Chinese commercial banking sector exhibited technological progress, and economies of scale were widespread across all Chinese commercial banks.